Detection of microfilariae (Nematoda: Filarioidea) in mosquito vectors trapped at bird and wildlife facilities in Durban, South Africa - Marufu, Munyaradzi Christopher (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2022.